A Post-Truth Campaign?: The Alternative for Germany in the 2019 European Parliament Elections. Issue 1 (1st March 2022) - Conrad, Maximilian
Abstract: This article analyzes the Alternative for Germany's campaign for the 2019 European Parliament elections against the backdrop of the phenomenon of "post-truth politics." Post-truth politics is operationalized here as the strategic deployment of misleading frames and argumentative as well as evaluative styles. This has become a standard tool in the repertoire of populist actors, and in German politics, the Alternative for Germany (AfD) is a case in point. Despite the party's thematic shift from issues of European integration to migration and multiculturalism, the European Union (eu ) still represents an important point of reference in the party's rhetoric. Empirically, this article addresses the importance of post-truth politics in the AfD's campaign by examining the frames and evaluative styles employed by the party and its leading candidates in evoking negative images of the eu, considering in particular social and other digital media as important venues for such processes.